2006
DOI: 10.1002/pbc.20726
|View full text |Cite
|
Sign up to set email alerts
|

Survival after relapse in children with solid tumors: A follow‐up study from the Italian off‐therapy registry

Abstract: Overall, patients with solid tumors who relapse after treatment discontinuation have a poor outcome, but significant differences exist according to the tumor types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 24 publications
1
26
1
Order By: Relevance
“…1) [11,16,79,81,87,88,90]. More specifically, HSC transplants, alone or in combination therapy, may be used for the treatment of patients with autoimmune diseases, refractory and severe aplastic anemias, congenital thrombocytopenia, osteoporosis, cardiovascular disorders, chronic inflammatory Bowel disorders (IBD) including Crohn's disease and ulcerative colitis, diabetes mellitus, leukemias, multiple myelanomas and Hodgkin's and non-Hodgkin's lymphomas and aggressive tumors [1,2,11,16,[57][58][59][60][93][94][95][96][97]. It has also been reported that MSCs, EPCs and their progenies can contribute to the regenerative process of several tissues including bone, cartilage, tendon, muscle, adipose, brain, lung, heart, pancreas, kidney and eye [98,99].…”
Section: Therapeutic Applications Of Bm-derived Stem/progenitor Cellsmentioning
confidence: 99%
“…1) [11,16,79,81,87,88,90]. More specifically, HSC transplants, alone or in combination therapy, may be used for the treatment of patients with autoimmune diseases, refractory and severe aplastic anemias, congenital thrombocytopenia, osteoporosis, cardiovascular disorders, chronic inflammatory Bowel disorders (IBD) including Crohn's disease and ulcerative colitis, diabetes mellitus, leukemias, multiple myelanomas and Hodgkin's and non-Hodgkin's lymphomas and aggressive tumors [1,2,11,16,[57][58][59][60][93][94][95][96][97]. It has also been reported that MSCs, EPCs and their progenies can contribute to the regenerative process of several tissues including bone, cartilage, tendon, muscle, adipose, brain, lung, heart, pancreas, kidney and eye [98,99].…”
Section: Therapeutic Applications Of Bm-derived Stem/progenitor Cellsmentioning
confidence: 99%
“…The clinical course of NB is influenced by several factors and among these disease stage plays an important role: patients with stage 1 and 2 will tend to have an excellent prognosis, with rates of 5-year disease-free survival (DFS), respectively, of 90 and 85 %, while those with stage 3 and 4 will have a poor prognosis, with rates of 40-60 and 15-25 %, respectively [5][6][7]. In this context, imaging modalities become determinant for a proper assessment of disease extension.…”
Section: Diagnostic Contextmentioning
confidence: 99%
“…Further treatment is available in phase I and phase II clinical trials that test new agents and combinations of agents against neuroblastoma, but the outcome remains very poor for relapsed high-risk disease. [21] Case Report: A 7 years old girl was admitted to the Dept of ENT & Head Neck Surgery, Dhaka Medical College Hospital with bilateral, non-tender, hard mass in the neck for 3 months with evening rise of temperature, without any sweating or chills. She had no complaints of pain, no bleeding, no wt.…”
Section: Neuroblastoma Neck In a 7-year-old Girl: A Very Rare Presentmentioning
confidence: 99%